Sagan Dalya Tea, a New "Old" Probable Adaptogenic Drug: Metabolic Characterization and Bioactivity Potentials of Rhododendron adamsii Leaves - Daniil N. Olennikov; Vyacheslav M. Nikolaev; Nadezhda K. Chirikova (MDPI AG, 2021)
Adams' rhododendron (Rhododendron adamsii Rehder) or Sagan Dalya tea is a famous Siberian evergreen medical plant of the Ericaceae family used in traditional medicines of Buryats, Yakuts, and Mongols as a tonic, stimulant, and adaptogenic drug. The high popularity of R. adamsii coupled with poor scientific knowledge prompted the addressing of gaps related to metabolic and biomedical data of Sagan Dalya tea. The application of solid-phase extraction and liquid chromatography-mass spectrometric techniques for the metabolomic study of R. adamsii leaf extracts resulted in the identification of more than 170 compounds, including carbohydrates, organic acids, simple phenol glycosides, triterpene glycosides, flavonoids, prenylated phenols, benzoic acid derivatives, hydroxycinnamates, dihydrochalcones, catechins, and procyanidins, most of which were identified for the first time in the plant. Extended surveys of the seasonal content of all detected compounds prove that specific metabolite variations reflect the bioactivity of R. adamsii extracts. Regarding in vitro methods, the expressed antioxidant potential of R. adamsii extracts was investigated via radical-scavenging, nitric oxide scavenging, and ferrous (II) ion chelating assays. The animal-based swimming to exhaustion test demonstrates the stimulating influence of R. adamsii extract on physical performance and endurance, concluding that the drug could act as an adaptogen. Thus, Sagan Dalya tea (R. adamsii) has confirmed its "old" application as a tonic remedy and requires further precise study as a novel adaptogenic plant.